Synthesis of oseltamivir conjugates with lactose analogs for inhibition studies on Trypanosoma cruzi trans-sialidase - Giorgi, María Eugenia (2011)
Trypanosoma cruzi, the agent of Chagas disease, expresses a unique enzyme, the trans-sialidase (TcTS) involved in the transfer of sialic acid from host glycoconjugates to mucins of the parasite. Crystallographic studies showed two sites in the catalytic region of TcTS, one binding the sialic acid donor and the other involved in binding terminal β-D-galactopyranosyl-containing compounds. We have previously described that lactose derivatives effectively inhibited the transfer of sialic acid to N-acetyllactosamine. On the other hand, oseltamivir is a sialic acid mimetic effective against some types of influenza virus. In this paper we report covalent conjugation of oseltamivir with lactose and lactobionolactone with the aim to obtain a bi-substrate potential inhibitor. The behavior of the new compounds in the TcTS reaction was studied.